Generalized model of blood flow in a vertical tube with suspension of gold nanomaterials: Applications in the cancer therapy - Imtiaz, A. (Tech Science Press, 2020)
Gold metallic nanoparticles are generally used within a lab as a tracer, to uncover on the presence of specific proteins or DNA in a sample, as well as for the recognition of various antibiotics. They are bio companionable and have properties to carry thermal energy to tumor cells by utilizing different clinical approaches. As the cancer cells are very smaller so for the infiltration, the properly sized nanoparticles have been injected in the blood. For this reason, gold nanoparticles are very effective. Keeping in mind the above applications, in the present work a generalized model of blood flow containing gold nanoparticles is considered in this work. The blood motion is considered in a cylindrical tube under the oscillating pressure gradient and magnetic field. The problem formulation is done using two types of fractional approaches namely CF (Caputo Fabrizio) and AB (Atangana-Baleanue) derivatives, whereas blood is considered as a counter-example of Casson fluid. Exact solutions of the problem are obtained using joint Laplace and Hankel transforms, and a comparative analysis is made between CF and AB. Results are computed in tables and shown in various plots for embedded parameters and discussed. It is found that adding 0.04-unit gold nanoparticles to blood, increase its heat transfer rate by 4 percent compared to regular blood. It is also noted that the heat transfer can be enhanced in the blood with memory. Â© 2020 Tech Science Press. All rights reserved.